70‐4L: Late‐News Paper: Large‐Area Single‐Layer Capacitive Touch Panel. Issue 1 (2nd June 2017) - Blush, Jason; Chase, Wes; den Boer, Willem; Bulea, Mihai; Day, Shawn; Hovden, Bjorn; Hsu, Andrew
Abstract : A 13 inch x 22 inch capacitive touch panel is presented with a single pattern transparent conductor. The touch panel uses a gradient sensor design enabled by a low haze, silver‐based transparent conductor with a sheet resistance of 7 ohm/sq that allows for scaling to larger sizes. The transparent conductor is patterned by laser ablation. The touch panel glass is one of two glass substrates in a rugged, laminated assembly.